Supply chain management strategies for small fast fashion firms: the case of the Dongdaemun Fashion District in South Korea. Issue 1 (2nd January 2016) - Seo, Min Jeong; Kim, Minjeong; Lee, Kyu-Hye
ABSTRACT: This paper contributes to the growing literature on fast fashion by examining how small fashion firms efficiently manage their supply chains in order to boost the supply efficiency of fast fashion. The results of a survey of manufacturing wholesalers in the Dongdaemun Fashion District (DFD) in South Korea suggest that lead times and wholesaler–retailer relationships which were linked to business performance had significant effects on supplier–wholesaler relationships. In turn, small fast fashion firms in the DFD retaining closer relationships with their buyers and suppliers were able to produce fast fashion more rapidly than were other rival firms. This paper provides useful implications for both practitioners and scholars in the fashion industry.